Image Compression Using Chain Coding for Electronic Shelf Labels (ESL) Systems - Kim, Youngjun; Kim, Ki Hyung; Cho, We Duke (IEEE Access, 2021)
One of the most important and recurring tasks in managing a store is to provide accurate, up-to-date price information to customers on the shelves. Manual updating of price tags has been a time-consuming, error-prone task with high labor costs. An Electronic shelf labels (ESL) system is becoming an attractive alternative for this task because of the dynamic-price-updating and customer's product-evaluation-display features. A common ESL system configuration in a retail store includes thousands of battery-powered ESL tags that are mostly connected wirelessly in a dense indoor environment. Raising the success ratio of wireless communication is essential for the system's viability due to its limited battery life. Most of the ESL traffic is the image data of goods that appear on the tags, and reducing the amount of the data is one of the most effective ways to enhance communication performance and reduce retransmission. This paper proposes an ESL image compression mechanism based on chain coding that utilizes ESL images' characteristics. The performance results show that the proposed mechanism could compress the ESL images smaller and decompress faster.
Keywords: Communication performance; Compression mechanism; Error prone tasks; Indoor environment; Price information; Product evaluation; System configurations; Wireless communications; chain code; Electronic shelf label; image compression